Re-thinking science-industry relations along the interactive model: The case of academic spin-offs - Jörg Potthast (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2009)
Academic spin-offs are private firms founded in direct connection with a transfer of knowledge or technology from public research facilities or universities. This direct relationship is established through patents or persons who transfer to the spin-off. Based on this definition the present contribution analyses interactions between public research institutions and academic spin-offs. Closely looking at a limited number of cases, a broad definition of interaction has been applied which includes flows of people (between both types of organisations), joint activities of knowledge production, and flows of money. With regard to three areas of research and innovation, namely IT, biotechnology and nanotechnology, the analysis of interactions has enabled the establishment of a finely grained picture of repercussions resulting from various forms of interaction. The analyses undertaken by research teams in Bulgaria, Finland, France, Germany, the Netherlands, Switzerland, and the UK are based upon approaches in the economics of innovation, organisational sociology, studies on higher education and science studies. – – Akademische Ausgründungen sind private Firmen, deren Gründung in direktem Zusammenhang mit einem Wissens- und Technologietransfer aus einer öffentlichen Forschungseinrichtung oder einer Hochschule steht. Diese unmittelbare Beziehung ist an Patenten oder an Personen zu erkennen, die in die Ausgründung wechseln. Auf der Grundlage dieser Definition analysiert der vorliegende Beitrag Interaktionen zwischen öffentlichen Forschungseinrichtungen und akademischen Ausgründungen. Anhand einer recht kleinen Zahl von Fallstudien wird dieser Begriff von ,,Interaktion“ weit ausgelegt. Interaktionen umfassen Bewegungen von Personen (zwischen beiden Typen von Organisationen), gemeinsame Aktivitäten der Wissensproduktion sowie Ressourcenströme. Für drei Forschungs- und Innovationsbereiche – IT, Biotechnologie und Nanotechnologie – führt die Analyse von Interaktionen zu einem feinkörnigen Bild der Rückwirkungen, die sich aus diesen Interaktionen ergeben. Der Beitrag geht auf ein EU-Forschungsprojekt mit Partnern in Bulgarien, Deutschland, Finnland, Frankreich, den Niederländen und aus dem Vereinigten Königreich zurück. Es werden Ansätze aus Innovationsökonomie, Organisationssoziologie, Hochschulforschung und Wissenschafts- und Technikforschung kombiniert.
Keywords: 300